Uji Efektivitas Fraksi Etil Asetat Eleutherine Bulbosa Terhadap Penurunan Kadar Kolesterol Total, Tekanan Darah Sistolik-Diastolik Pada Tikus Putih Jantan - Haliza Diny Fauzia; Miming Andika; Putri Nilam Sari; Rizqa Hasanah; Fajrian Aulia Putra; Oryza Sativa Fitriani; Nola Rahmadasmi (JURNAL FARMASI DAN MAKANAN, 2024)
Eleutherine Bulbosa is one of the plants cultivated by the community for traditional medicine. It's like lowering hypercholesterolemia. Hypercholesterolemia is a condition characterized by high levels of cholesterol in the blood. Besides, it can also lower hypertension. Hypertension is a condition in which blood pressure exceeds the normal limit, with systolic pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. The study aims to look at the effectiveness of the Eleutherine Bulbosa ethyl acetate fraction against the reduction in total cholesterol levels, systolic blood pressure, and diastolic blood pressure in male white rats. Animal cholesterol levels were raised using MLT for 22 days. Cholesterol parameters were tested using a Dumolab DC20 photometer. The inducer used to raise blood pressure is 8% NaCl for 14 days. Blood pressure is measured using non-invasive blood pressure. (NIBP). The results of the research showed that the flavonoid groups that play a role in lowering high cholesterol levels are the anthocyanins and quercetin, while the alkaloid compounds play a part in lowering high blood pressure. Data analysis showed significant results (p<0.05). It can be concluded that the administration of the ethyl acetate fraction Eleutherine Bulbosa is capable of lowering high cholesterol levels and high systolic-diastolic blood pressure.